Emergence of socio-economic geography and spatial management as a scientific discipline in the new classification of science in Poland - Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2021)
The aim of the article is to present the chronology of activities that led to the emergence of the discipline ‘socio-economic geography and spatial management’ in the new classification of science in Poland which has been in force since 2018. The path of emergence of the discussed discipline is analysed from the standpoint of one of the participants of this process. The article also presents positive and negative consequences of implementing this classification in the context of two different structural models of geography as a science. Among positive consequences one can mention (1) preservation of the name ‘geography’ on the list of scientific disciplines, and (2) a favourable formal and legal ‘empowerment’ of socio-economic geography in the system of the organisation and evaluation of science in Po land. Among the greatest threats one can see (1) a reduction in the importance of socio-economic geography in favour of spatial management, and (2) the organisational disintegration of some geographical communities, institutions and research units. However, there are also attempts at the reintegration of geography around two of its basic segments, i.e. physical geography and human geography. In the author’s opinion, future activities should focus on the means to strengthen realistically (and not only declaratively) the position of the new discipline and its constituent subdisciplines against other scientific disciplines.